SYSTEMATIC LITERATURE REVIEW: PENGGUNAAN MEDIA INTERAKTIF SCRATCH PADA PENINGKATAN KEMAMPUAN NUMERASI SISWA SD - Fikriyah, Nurul; Wiryanto; Istiq'faroh, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Numeracy ability is a person's ability to solve problems using mathematical knowledge. With numeracy, it is hoped that it can help in organizing, assessing an action in order to get maximum results in dealing with problems in daily life. If learning mathematics without using media, students will become bored and have no motivation to learn. For this reason, digital-based interactive media is needed in accordance with the increasingly rapid development of technology. The purpose of this study is to describe the use of scratch interactive media in improving the numeracy skills of elementary school students. Method used The research method used this time is Systematic Literature Review (SLR). Systematic Literature Review (SLR) can be interpreted as a process of identifying, evaluating, and interpreting the results of existing research with the aim of presenting specific answers. The results of the study show that the use of scratch can increase creativity in mathematical thinking, logical thinking, earnestness in following lessons, a sense of fun, a sense of enjoyment and make it easier to learn mathematics because with scratch students learn to use games and can make their own math games, so it is very helpful in improving the numeracy skills of elementary school students. In conclusion, using scratch interactive media can improve the numeracy skills of elementary school students